Age and gender based study of urine microscopy in children and adolescents: a retrospective study - Umman, Philip; Philip, Tinu; Babu, Hana George; Thomas, Pramod (International Surgery Journal, 2022)
Background: Urinary tract infection (UTI) is a common reason for accessing health care services in all age groups. Women are more susceptible to UTI across age groups. Among males, the prevalence decreases in adolescence. Socio-economic and behavioural factors may play a significant role in the higher prevalence of UTI among adolescent girls. A study on UTI among children and adolescents will give a better insight in to the gravity of the problem and suggest appropriate interventions. Aim of the current study was to investigate the prevalence of urinary tract infection in males and females in the age group 0 to 20 based on the urine routine examination. Methods: This retrospective study included patients who had urine routine examination (URE) done based on clinical symptoms, during the period from January to December 2018 in a tertiary care teaching hospital. Data was obtained from the laboratory records and medical records department. Results: 1574 (3.43%) out of 45896 patients had a URE. This included 716 males (46%) and 858 females (54%). Among those with positive URE results, females were more affected than their male counterparts and this was statistically significant (male 21.8%, female 78.2%, p< 0.0001). As age advances, the prevalence decreases in males. Conclusions: Urinary tract infection is more prevalent in females across the pre- adolescent and adolescent age group. It decreases with age in males. Understanding the factors responsible for the persistent higher prevalence in females may decrease the prevalence of urinary infection in adolescent females.